La turbidimetría una metodología promisoria para caracterizar la estabilidad estructural de los suelos - Castillo Franco, J.A.; Amézquita Collazos, Edgar; Muller-Samann, KM (2000)
In two hillside areas in the north of the Cauca department, with mean annual rainfalls between 1600 and 2400mm and soils classified as Inceptisols, erosion plots were established and several different soil management systems were evaluated during seven years. The turbidimetry technique was used with soil samples from the treatments to characterize structural stability of the aggregates. The method is based upon the fact that water as an extrinsic factor of the soil is an important agent in the destruction of the aggregates, causing the formation of smaller aggregate units and the dispersion of the finest materials (clays). Aggregates with diameters between 1-2 and 2-4mm from the different treatments were evaluated. Concentration readings were made for the first two minutes and 2 hours after the experiment. Results show that differences exist regarding the stability of aggregates between the crop rotations evaluated and that the technique is sensitive to the determination of structural stability of soils under different cultivation systems, including the input of organic materials. It was also observed that there is a clear tendency to a higher concentration of soil particles in the suspension when the aggregates are finer, this response being approximate to the results obtained when said aggregates were exposed to a rainfall simulator.